PEMANFAATAN CROTALARIA RETUSA (L.) DAN â€œKASCINGâ€ SEBAGAI PUPUK ORGANIK UNTUK SAYURAN SELADA (Lactuca Sativa) - Sudjana, Briljan (Majalah Ilmiah SOLUSI, 2015)
The purpose of the experiment was to study the effect of Crotalaria retusa (L) and casting on Lactuca sativa (lectuce). The field experiment in Karawang International Industrial City (KIIC) was arranged in a Factorial Randomized Block Design with two factors. The first factor was dosage of Crotalaria retusa (L) consisted of three levels:0, 3.5, and 7 tons per hectare. The second factors was dosage of casting with three levels: 0, 3.5, and 7 tons per hectare. All of those organic matters were apllied two weeks before planting. The results showed that the organic matters increased leaves dry weight, yield, and total of leaves of Lactuca sativa.The combination of 3.5 tons of Crotalaria retusa (L.) and 3.5 tons of casting has given the highest results on the two parameters ealier mentioned. And, on dosage of 7.5 tons of the both organic treated are best for total leaves Key words: Organic matters, Crotalaria retusa (L), casting, Lactuca sativa